The Definition and Scope of Philosopichal Inquiry - Fauzan Abdillah Syihab; Ramsiah Tasruddin (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to dissect in depth the nature of philosophy and its scope of study as the foundation of scientific thinking. As the